An Introduction to Egalitarian Thought and Dynamics. Issue 3 (1st September 2022) - Rio, Knut; Kapferer, Bruce; Bertelsen, Bjørn Enge
Abstract: In this introduction we approach egalitarianism as an upsetting force that in various ways has shaped much of modern, especially Western, human history. We outline philosophical trajectories from the Enlightenment onward; consider the historical realization of an agency of 'the people' for the articulation of state, society, and politics; and highlight some issues that arise when the claims to freedom and equality clash against established institutions and values. Stressing the dynamic intertwining of the egalitarian with the hierarchical, we portray egalitarian life forms as modes of relationality that negate, subvert, or take advantage of open potentials in existing systems. Egalitarian life strives toward reconfiguring social orders through rupturing moments of effervescence and liminality while attempting to redefine central categories of life.